Stepwise atmospheric carbon-isotope excursion during the Toarcian Oceanic Anoxic Event (Early Jurassic, Polish Basin) - Hesselbo, S; Pienkowski, G (2011)
During the Mesozoic (250-64. Ma) intervals of about 0.5. Myr were subject to severe environmental changes, including high sea-surface temperature and very low oxygen content of marine water. These Oceanic Anoxic Events, or OAEs, occurred simultaneously with profound disturbance to the carbon cycle. The carbon-isotope anomaly in the Early Jurassic that marks the Toarcian Oceanic Anoxic Event (T-OAE) at ~. 182. Ma is characterized in marine sections by a series of dramatic steps towards lighter values. Herein we present new carbon-isotope data from terrestrial organic matter (phytoclast separates), collected through a Late Pliensbachian-Middle Toarcian coastal and marginal marine succession in the Polish Basin, a setting where hinterland climate and sea-level change are well recorded. The results show that the shift to light carbon-isotope values in the woody organic matter, and therefore also in atmospheric carbon dioxide, similarly occurred in major steps. The steps are here correlated with those identified from marine organic matter, where they have previously been attributed to 100. kyr eccentricity forcing of climate. The results provide strong support for orbitally and climatically controlled release of isotopically light carbon from gas hydrates into the ocean-atmosphere system in a series of rapid bursts. Additionally, a link between the carbon-isotope steps and shoreline movements can be demonstrated. Individual peaks of the negative excursion are mostly associated with facies indicative of sea-level rise (flooding surfaces). However, at the same time inferred higher atmospheric carbon-dioxide content may be expected to have resulted in increased rainfall and temperature, leading to accelerated weathering and erosion, and consequently increased sediment supply, progradation and regression, causing some mismatches between isotope shifts and inferred sea-level changes. Enhanced abundance of megaspores derived from hydrophilic plant groups, and marked increase in kaolinite, are coincident with the overall development of the negative isotope excursion. The combined data suggest that each 100-kyr cycle in carbon-isotope values was characterized by increasingly severe palaeoclimatic change, culminating in extremely hot and humid conditions co-incident with the peak of the final most negative carbon-isotope excursion. The chemostratigraphic correlation allows very precise dating of the Late Pliensbachian-Middle Toarcian coastal and marginal marine sedimentary succession in the Polish Basin. © 2010 Elsevier B.V.